(untitled) (Orthodontic Journal of Nepal, 2015)
This article overviews the effects of debonding procedures on tooth enamel and reviews a variety of mechanical methods that have been designed to achieve satisfactory composite removal with minimal damage to the enamel surface. The orthodontic procedures starting from etching, priming to debonding cause irreversible enamel loss. The orthodontic treatment should ensure benefit to the patient; the advantages of treatment should far outweigh any adverse sequelae that might cause by the treatment. To prevent, minimize and manage the possible adverse effects of debonding mechanics, the clinician should be aware of the problems that may occur during the treatment procedures.